The action for higher spin black holes in three dimensions - Bañados, Máximo; Canto, Rodrigo; Theisen, Stefan (Journal of high energy physics, 2012)
In the context of (2+1)-dimensional Chern-Simons SL(N, RR \mathbb{R} ) × SL(N, RR \mathbb{R} ) gauge fields and spin N black holes we compute the on-shell action and show that it generates sensible and consistent thermodynamics. In particular, the Chern-Simons action solves the integrability conditions recently considered in the literature.
Gesehen am 25.09.2018